Pengaruh Citra Merek dan Kualitas Layanan dengan Variabel Intervening Minat Beli terhadap Keputusan Pembelian di TK ID - Saputri, Nindi; Sudhana, Pranakusuma (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
Education is a necessity for anyone from any background, because it is believed to bring change to be the better person, this view makes education always in demand and will never be abandoned. Indonesia has plenty of school-aged people, one of them are in the kindergarten level. his statement is not in-line with the phenomenon of the decreasing number of students in ID Kindergarten, Z Foundation, JPBS Branch in 2019. The emergency situation of the Covid-19 Pandemic has made parents postponed their children to school. In addition, the brand image and quality of services of a school are considered in choosing a school. This study aims to explore more about the influence of brand image, service quality, buying interest on purchasing decisions. This Quantitative research is using questionnaire instruments and processed using the structure equation technique of partial least squat (SEM-PLS) model. The results of this study show that buying interest could strengthen the connection between brand image, service quality and purchasing decisions at TK ID.